2019
DOI: 10.1007/s00264-019-04452-5
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric correlation with hamstring graft size in anterior cruciate ligament reconstruction among males

Abstract: Purpose Pre-operative knowledge of hamstring graft size for anterior cruciate ligament reconstruction (ACL) is of clinical importance and useful in making appropriate decisions about graft choice. This study investigated if there is any correlation between anthropometric measurements such as height, weight, body mass index, thigh length, and circumference with the size of hamstring tendon graft in anterior cruciate ligament reconstruction. Methods The anthropometric data of 50 consecutive adult males, who unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 23 publications
2
49
0
Order By: Relevance
“…It has previously been shown that the graft diameter is not related to BMI, as demonstrated in multiple separate studies [ 18 , 21 , 23 , 24 , 26 , 27 ]. Our analysis exhibits a similar finding regarding BMI.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…It has previously been shown that the graft diameter is not related to BMI, as demonstrated in multiple separate studies [ 18 , 21 , 23 , 24 , 26 , 27 ]. Our analysis exhibits a similar finding regarding BMI.…”
Section: Discussionmentioning
confidence: 90%
“…Similarly, our study found no statistically significant correlation between age and graft diameter, as has also been demonstrated before [ 18 - 21 , 24 , 26 ]. Although a study by Moghamis et al, in contrast, reported a moderately significant positive correlation between age and the harvested graft diameter, there was no correlation with height or BMI [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another limitation is that at least in one of five patients, the length of ST tendon, may be inadequate to be used alone as a four-strand graft (especially in females). 20 , 21 In order to ensure more intratunnel graft length, tripling the ST and gracilis harvesting should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…A standard guide (Smith & Nephew) was used in the measurement of the graft diameter (the smallest calibrated size through which the graft could pass). 12 An endobutton (Endobutton CL Ultra; Smith & Nephew) was used for femoral fixation. Tibial fixation was achieved using an appropriately sized bioabsorbable screw (Biosure HA; Smith & Nephew) and a staple (Smith & Nephew) when the knee was in full extension.…”
Section: Surgical Techniquementioning
confidence: 99%